Adsorção de leuco verde malaquita em biocarvão sintetizado a partir de coroas de abacaxi.2020 - Santos, Cynthia Pereira dos (2020)
Lignocellulosic biomass from agroindustrial waste have been used as a precursor in the synthesis of biochar. The biochar can be applied as an adsorbent material for the adsorption process, making this process more viable and inexpensive than the process w